The changes of carotene in the process of obtaining food additives on the basis of carrots - Bandurenko, Galina; Bessarab, Alexander; Levkivska (Muzika), Tetiana (My University, 2014)
The work proposed a comprehensive resourcesaving technology of processing of carrots with getting two basic products that contain carotene - dry and liquid. The obtained products containing carotene, can be used in food technology as а multifunctional enriching additives. В роботі запропонована комплексна ресурсозберігаюча технологія переробки моркви з одержанням двох каротиновмісних продуктів – рідкого та сухого. Одержані каротиновмісні продукти можна використовувати в різних харчових технологіях як багатофункціональні збагачуючі добавки.
Keywords: carrot; enriching additives; β-carotene; морква; β-каротин; збагачуючі добавки; морковь; обогащающие добавки; кафедра технології консервування